UTANG LUAR NEGERI; PARADOKS PEMBANGUNAN EKONOMI INDONESIA - Pellu, Arifin (AMAL: Jurnal Ekonomi Syariah, 2019)
This article aims to look at the relevance of Indonesia's foreign debt with its contribution to development accompanied by a study of sharia economics on debt. The amount of Indonesia's foreign debt continues to swell. Government savings that are expected to reduce the burden of external debt cannot reduce the burden of external debt. In fact, it has even added to the burden of external debt to penetrate Rp5,410 trillion. Indonesia is one of the countries that still rely on foreign aid to fund development, whether through loans or debt or foreign grants. The government does not have a strong commitment to pay off foreign debt. Instead of paying off, the government is diligently adding new debt without paying attention to the balance (balance) balance of payments. The development process carried out is the process of "digging a manhole cover". This is the paradox of Indonesia's foreign debt. While from the perspective of Islamic economics, external debt cannot be released from interest (usury). Riba is a big sin that must be shunned by Muslims as far as possible. As Allah SWT said in QS al-Baqarah (2): 275, 286 and also Qs. An-Nisaa verse 141, Hadith narrated by Muslim and Hadith narrated by Ibn Majah. In Islam there are forms of cooperation that are permitted in sharia, such as Mudharabah, Musyarakah, Murabahah, etc., can be developed as a form of external financing in the state budget. These forms are in principle more flow creating equity than flow creating debt, this form is implemented by the Islamic Development Bankhas funded many projects in Islamic countries with this scheme. Keyword: Foreign debt,paradox, development